Associated factors of acute primary angle closure glaucoma in a sub-group of Chinese people: comparison between attack eyes and normal controls. Issue 1 (December 2017) - Liu, Lifang; Liu, Xinyu; Huang, Chukai; Wang, Geng; Ma, Di; Zhang, Wanqi; Zheng, Ce; Zhang, Mingzhi
Abstract Acute primary angle closure glaucoma (APACG) is an ophthalmic emergency that may lead to irreversible blindness. Although efforts were made to control intraocular pressure, disease progression still existed. Anterior segment optical coherence tomography (AS OCT) may provide a new insight into mechanism of APACG. In order to seek out associated factors by AS OCT, We compared anterior segment parameters between 74 APACG and 48 normal eyes. Analysis of variance, principle component analysis and logistic regression were used. APACG group had more women (75.7% vs 47.9%, p = 0.002), smaller anterior chamber (anterior chamber depth, ACD; anterior chamber area, ACA; all p = 0.001), narrower angle (AOD500, AOD750, angle opening distance at 500um and 750um; TISA500, TISA750, trabecular-iris space area at 500um and 750um; ARA500, ARA750, angle recess area at 500um and 750um; all p < 0.001), thinner iris (iris thickness at 750um, IT750; maximum of iris thickness, ITMAX; all p < 0.001), larger iris area (IA, p < 0.001) and lens vault (LV, p = 0.005). Principle component extracted were AOD500, AOD750, TISA500, TISA750, ARA500, ARA750, IA, PD (pupillary diameter), ACD, ACA and IT750. After adjusting for confounding factors, AOD750 (b = 12.40 ± 2.56, p < 0.001), IT750 (b = 10.50 ± 3.45, p = 0.002) and IA (b = −1.56 ± 0.77, p = 0.044) were significantly associated with occurrence of APACG.